Analysis of 10 years of accidents with biological material among the nursing staff - Dayane Xavier de Barros; Anaclara Ferreira Veiga Tipple; Liwcy Keller de Oliveira Lopes Lima; Adenícia Custódia Silva e Souza; Zilah Cândida Pereira das Neves; Thaís de Arvelos Salgado (Universidade Federal de Goias, 2016)
The objectives of the present study were: to identify the profile of accidents with biological material among nursing professionals treated in a reference service; to characterize pre-exposure conducts and to analyze factors associated with percutaneous exposure. An epidemiological, retrospective and analytical study was conducted in records of accidents involving biological material from 2000 to 2010. The number of accidents with the nursing staff was 2,569, representing 44.6% of the total records. There was a prevalence of percutaneous exposure cases involving needles with lumen and blood in upper limbs among female nursing technicians. Being female and working outside the city where the service is located increased about twice the chances of suffering percutaneous accidents. The data found strengthen the importance of biological risk in the nursing practice and point to the fact that workers have to move between cities to be treated when the accident is considered serious, such as the case of percutaneous accidents.